Remodeling of the gut microbiome by Lactobacillus johnsonii alleviates the development of acute myocardial infarction - Zhong, Xinqin; Zhao, Yucui; Huang, Lu; Liu, Jiarui; Wang, Kaiyue; Gao, Xiumei; Zhao, Xin; Wang, Xiaoying (Frontiers in Microbiology, 2023)
Introduction: The gut microbial community, which can be disturbed or repaired by changes in the internal environment, contributes to the development of acute myocardial infarction (AMI). Gut probiotics play a role in microbiome remodeling and nutritional intervention post-AMI. A newly isolated Lactobacillus johnsonii strain EU03 has shown potential as a probiotic. Here, we investigated the cardioprotective function and mechanism of L. johnsonii through gut microbiome remodeling in AMI rats. Methods: A rat model of left anterior descending coronary artery ligation (LAD)-mediated AMI was assessed with echocardiography, histology, and serum cardiac biomarkers to evaluate the beneficial effects of L. johnsonii. The immunofluorescence analysis was utilized to visualize the intestinal barrier changes. Antibiotic administration model was used for assessing the gut commensals’ function in the improvement of cardiac function post-AMI. The underlying beneficial mechanism through L. johnsonii enrichment was further investigated by metagenomics and metabolomics analysis. Results: A 28-day treatment with L. johnsonii protected cardiac function, delayed cardiac pathology, suppressed myocardial injury cytokines, and improved gut barrier integrity. The microbiome composition was reprogrammed by enhancing the abundance of L. johnsonii. Microbiome dysbiosis by antibiotics abrogated the improvement of cardiac function post-AMI by L. johnsonii. L. johnsonii enrichment caused remodeling of gut microbiome by increasing the abundance of Muribaculaceae, Lactobacillus, and decreasing Romboutsia, Clostridia UCG-014, which were correlated with cardiac traits and serum metabolic biomarkers 16,16-dimethyl-PGA2, and Lithocholate 3-O-glucuronide. Conclusion: These findings reveal that gut microbiome remodeling by L. johnsonii ameliorates the cardiac function post-AMI and might advance microbiome-targeted nutritional intervention.